2021
DOI: 10.1186/s12954-021-00499-z
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and changes in pattern of drug use among participants at the Stockholm Needle Exchange Program during the COVID-19 pandemic

Abstract: Background and aims People who inject drugs may be particularly vulnerable to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) due to underlying health problems, stigma and social vulnerabilities. Harm reduction services, including needle exchange programs (NEP), have been subjected to varying degrees of disruption in the world, especially in the beginning of the coronavirus disease 2019 (COVID-19) pandemic. Compared to responses in other countries, Sweden’s initial strategy tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…Reports in the literature of SARS-CoV-2 prevalence among people who inject drugs are sparse. In a study of needle exchange clients in Stockholm, Sweden, SARS-CoV-2 prevalence was 5.4% [ 12 ], whereas in a survey of people who inject drugs in England, Wales and Northern Ireland, 11% reported that they had tested positive for COVID-19 [ 13 ]. U.S. estimates among people who are homeless or living in shelters range from 2%-14% [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reports in the literature of SARS-CoV-2 prevalence among people who inject drugs are sparse. In a study of needle exchange clients in Stockholm, Sweden, SARS-CoV-2 prevalence was 5.4% [ 12 ], whereas in a survey of people who inject drugs in England, Wales and Northern Ireland, 11% reported that they had tested positive for COVID-19 [ 13 ]. U.S. estimates among people who are homeless or living in shelters range from 2%-14% [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported reduced access to harm reduction services owing to the pandemic [48,52,61] though only one study inferred that this was related to a subsequent rise in DRDs [41]. More recent research has provided further evidence of the impacts of reduced service access including reductions in uptake of injecting equipment and MAT as well as a reduction of uptake of HIV and other BBV testing in Spain, UK and Sweden [75][76][77]. However, one recent study conducted in Sweden [76], which unlike many other countries did not impose a general societal lockdown, reported that harm reduction services were accessed as usual (at worst) during the initial stages of the pandemic and that distribution of needles and syringes increased.…”
Section: Reduced Access To Treatment and Harm Reduction Servicesmentioning
confidence: 99%
“…As many PWID experience pervasive stigma and social exclusion, social distancing is a practice that many may be familiar with or even prefer (Neale, 2008 ; Schlosser & Harris, 2020 ). Despite this, protective measures and risk factors among PWID appear to be similar to the general population, and this knowledge does not necessarily translate to a willingness to fully comply with the COVID‐19 recommendations such as social distancing, home isolation and vaccinations as seen in a study conducted in Sweden between July 27 and October 2020, where 232 clients of needle exchange programs responded to COVID‐19 Health Literacy Questionnaire and 779 CoV‐2 IgG antibody tests were performed (Lindqvist et al., 2021 ). PWID face structural barriers to vaccination such as inadequate access to transportation and mistrust of health services which may impact vaccine uptake (Fisk, 2021 ; Vasylyeva et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%